EVALUASI DAYA BACA MAHASISWA TERHADAP MODUL KULIAH (STUDI KASUS MATAKULIAH METODE PENELITIAN): Evaluation, Module - -, Riswan (JURNAL AKADEMIKA, 2019)
This research was conducted to evaluate the readability of students towards the lecture module of the research method. Academics ask each lecturer to make lecture modules to help students understand lecture material. In the research method module, researchers as lecturers conduct evaluation of each module that has been studied. This evaluation is done online. In this evaluation the author emphasizes chapter 1. With this evaluation, it is expected that the general objectives and specific instructional objectives of the course will be achieved properly. Students have a basic foundation of pre-lecture, and can re-learn the material that has been delivered by lecturers in the class. In general, the material for this research method module is adjusted to the weight of the course. The results of the evaluation of the students 'reading power toward the module research method on the 14 questions asked illustrated the students' insight into their reading power toward the module with an average of 52, 78/80 rating points, median 50/80, with a range of values ​​ranging from 20 to 70.